A Pronoun Analysis of Couples’ Support Transactions - Hinnekens, Céline; Lemmens, Gilbert; Vanhee, Gaëlle; Verhofstadt, Lesley (Frontiers in Psychology, 2016)
The present study collected data about couples’ level of relationship quality and their usage of pronouns that express we-ness or separateness in the context of support interactions. The sample consisted of 48 couples in a long-term relationship who provided questionnaire data and participated in two videotaped social support interaction tasks. Couples’ videotaped interactions were subsequently coded for the number of personal pronouns—we-words (e.g., we, ours, ourselves) versus you and me-words (e.g., me, mine, you, yours)—used by both partners.